2021
DOI: 10.1021/acs.est.1c01520
|View full text |Cite
|
Sign up to set email alerts
|

Native Bacterial Community Convergence in Augmented and Stimulated Ureolytic MICP Biocementation

Abstract: Microbially induced calcite precipitation is a biomineralization process with numerous civil engineering and ground improvement applications. In replicate soil columns, the efficacy and microbial composition of soil bioaugmented with the ureolytic bacterium Sporosarcina pasteurii were compared to a biostimulation method that enriches native ureolytic soil bacteria in situ under conditions analogous to field implementation. The selective enrichment resulting from sequential stimulation treatments strongly selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Therefore, the urease activity generated by cells in the columns would be exhausted probably because there was no nutrient source in the precipitation solution. Graddy et al ( 2021 ) investigated feeding Sporosarcina pasteurii in natural sands. The results indicated that native species of Sporosarcina quickly outcompeted feeding cells (Graddy et al 2021 ) most probably they are spore formers, and spores are difficult to kill even by autoclaving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the urease activity generated by cells in the columns would be exhausted probably because there was no nutrient source in the precipitation solution. Graddy et al ( 2021 ) investigated feeding Sporosarcina pasteurii in natural sands. The results indicated that native species of Sporosarcina quickly outcompeted feeding cells (Graddy et al 2021 ) most probably they are spore formers, and spores are difficult to kill even by autoclaving.…”
Section: Discussionmentioning
confidence: 99%
“…Graddy et al ( 2021 ) investigated feeding Sporosarcina pasteurii in natural sands. The results indicated that native species of Sporosarcina quickly outcompeted feeding cells (Graddy et al 2021 ) most probably they are spore formers, and spores are difficult to kill even by autoclaving.…”
Section: Discussionmentioning
confidence: 99%
“…Biostimulation achieves MICP by stimulating the growth of native microorganisms with desirable metabolic capabilities using an enrichment and nutrient medium ( Gat et al, 2016 ). It is cost-effective and environmentally viable, since indigenous soil strains may have advantages in survivability and adaptability ( Graddy et al, 2021 ), making them compatible with the applied polluted environment ( Gat et al, 2016 ; Dhami et al, 2017 ; Graddy et al, 2018 ). For instance, the biostimulation process that applied to accelerate MICP in Cu immobilization also yielded favorable results; specifically, from 45.54 mg/kg, the exchangeable soluble fraction of Cu in soil fell to 1.55 mg/kg ( Chen and Achal, 2019 ).…”
Section: Key Factors Influencing the Performance Of Micp Bioremediationmentioning
confidence: 99%
“…Noteworthy, indigenous microorganisms distributed within the soil environment can be enriched in situ (bio-stimulation) by modifying local environmental conditions which favour the diversity and distribution of existing bacterial community with required urease capabilities for various MICP applications (Gowthaman et al 2019;Graddy et al 2021). Thus, it confirms the promising nature of utilizing indigenous urease-producing bacteria as agents for MICP applications.…”
Section: Introductionmentioning
confidence: 99%